Activation of futile cycles as an approach to increase ethanol yield during glucose fermentation in Saccharomyces cerevisiae. Issue 2 (2nd April 2016) - Semkiv, Marta V.; Dmytruk, Kostyantyn V.; Abbas, Charles A.; Sibirny, Andriy A.
ABSTRACT: An increase in ethanol yield by yeast from the fermentation of conventional sugars such as glucose and sucrose is possible by reducing the production of a key byproduct such as cellular biomass. Previously we have reported that overexpression of PHO8 gene encoding non-specific ATP-hydrolyzing alkaline phosphatase can lead to a decrease in cellular ATP content and to an increase in ethanol yield during glucose fermentation by Saccharomyces cerevisiae . In this work we further report on 2 new successful approaches to reduce cellular levels of ATP that increase ethanol yield and productivity. The first approach is based on the overexpression of the heterologous Escherichia coli apy gene encoding apyrase or SSB1 part of the chaperon that exhibit ATPase activity in yeast. In the second approach we constructed a futile cycle by the overexpression of S. cerevisiae genes encoding pyruvate carboxylase and phosphoenolpyruvate carboxykinase in S. cerevisiae . These genetically engineered strains accumulated more ethanol compared to the wild-type strain during alcoholic fermentation.